STUDI KASUS PENOLAKAN SOSIAL PADA PESERTA DIDIK - Agustina, Puput Radha; Yusuf, Abas; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Â AbstractThe purpose of this study is to reveal how students who experience social rejection in SMP Negeri 12 Pontianak. This research method is descriptive in the form of case study research. The case subjects in this study were two people.. Data collection techniques in this research were observation, interview and sociometry questionnaire. Research data collection tools are observation guides and interview guides To overcome the problems experienced subjects I and II, Alternative help given to the subject of the case 1 is a model of counseling Rational Emotive Behavioral Therapy (REBT) using cognitive dispute techniques and rational analysis, whereas alternative assistance given to the subject of the case is a model of counseling Behavioral Therapy with formation techniques shaping and aversion therapy (Covert sensitization). The results obtained after being given alternative assistance on the subject of case one, experienced many changes, especially in socializing with peers at school. While case two subjects can control themselves not to disturb their friends in class. The researcher's suggestion is that case subjects are expected to be able to maintain and enhance positive change.Keywords :Case Studies, Social Rejection